Determinants of System of Rice Intensification Adoption and its Impacts on Rice Yield in the Upland Region of Central Vietnam - Nguyen, Hang Thi Thuy; Hung, Pham Xuan (Asian Journal of Agriculture and Rural Development, 2022)
The System of Rice Intensification (SRI) is an eco-friendly approach that aims to increase rice yield, reduce required inputs, and improve rural households’ income without burdening the environment. This paper investigates the factors that influence the adoption of the SRI practice in rice production and the impact of the SRI adoption on rice yields in the upland region of Central Vietnam. Utilizing the stratified random sampling method, 239 rice farmers in Quang Nam and Thua Thien Hue provinces were selected for the study. Our study employed the logit model to identify the determinants of SRI adoption and found that the age of respondents had a significant and negative effect on the adoption of SRI. In contrast, the amount of family labor, number of plots, and access to credit had significant positive effects on farmers’ decision to adopt SRI. In addition, the results showed that when rice farmers adopted SRI, their yields increased by 15.1% on average. Regarding the policy implications, the results suggest a need for a coordinated policy between the Vietnamese government and farmers to support the implementation of the SRI method in mountainous areas, especially to train farmers to use the SRI technique.